Inspiratory muscle warm-up improves 3,200-m running performance in distance runners - Barnes, K. R.; Ludge, A. R. (The Journal of Strength and Conditioning Research, 2021)
This study examined the effects of an inspiratory muscle exercise as part of a warm-up (IMW) using a resisted breathing trainer on running performance. In a randomized crossover design, 17 trained distance runners completed two 3,200-m performance trials on separate days, preceded by 2 different warm-up procedures: IMW or sham IMW (CON). In each condition, subjects performed 30 breaths against either 50% of each athlete's peak strength (IMW) or 30 slow protracted breaths against negligible resistance (CON). Perceived race readiness and inspiratory muscle strength, flow, power, and volume were measured before and after each warm-up. Heart rate (HR), rating of perceived exertion (RPE) and dyspnea (RPD), and expired gases were collected during each trial. A 3,200-m run performance was 2.8% ± 1.5% (20.4-second) faster after IMW (effect size [ES] = 0.37, p = 0.02). After each warm-up condition, there was as small effect on peak inspiratory strength (6.6 ± 4.8%, ES = 0.22, p = 0.02), flow (5.2 ± 4.4%, ES = 0.20, p = 0.03), power (17.6 ± 16.7%, ES = 0.22, p = 0.04), and volume (6.7 ± 6.3%, ES = 0.24, p = 0.01) after IMW compared with CON. There were no differences in HR, minute volume, peak Vo2, or Vo2 at each 800-m interval between conditions (ES = 0.13, p > 0.17). There were small differences in RPE at 800 m and 1,600 m (ES = 0.32, p = 0.17; ES = 0.21, p = 0.38, respectively), but no difference at the last 1,600 m (p = 1.0). There was a moderate positive effect on RPD (ES = 0.81, p < 0.001) and race readiness (ES = 0.76, p < 0.01) after IMW. Overall, the data suggest that IMW improves 3,200-m performance because of enhancements in inspiratory muscle function characteristics and reduction in dyspnea.